Effect of addition of BT on relaxor behavior of PIN-PT ceramics - Supattra Wongsaenmai (2018)
Ferroelectric ceramics with chemical formula (l-x)Pb(In0.5Nb0.5)O3-xPbTiO3and (1-x)Pb(In0.5Nb0.5)O3-xPbTiO3with 20%mol of BT (x = 0.0, 0.1, 0.2 and 0.3) were prepared via the wolframite method. The relaxor behavior was analyzed from the dielectric properties and thermal expansion measurements. The dielectric properties were measured at frequencies between 100 Hz and 100 kHz whereas the thermal expansion was measured in the temperature range between - 145°C and 500°C. It is found that the addition of BT effects the relaxor behavior of PIN-PT system. The broad and diffused dielectric constant maxima and essentially no change in Burns temperature were measured and thus suggesting the glassy polarization and relaxor behavior in the PIN-PT-BT compositions.